New Paradigms in Cell Therapy: Repeated Dosing, Intravenous Delivery, Immunomodulatory Actions, and New Cell Types. Issue 2 (6th July 2018) - Wysoczynski, Marcin; Khan, Abdur; Bolli, Roberto
Abstract : Perhaps the most important advance in the field of cell therapy for heart disease has been the recognition that all stem/progenitor cells (both adult and embryonic) fail to engraft in the heart to a significant extent and thus work via paracrine mechanisms. This fundamental advance has led to 4 new paradigms that are discussed in this review and that may importantly shape, or even revolutionize, the future of the field: (1) repeated cell therapy, (2) intravenous cell therapy, (3) immunomodulatory actions of cell therapy, and (4) new cell types. Because virtually all of our current knowledge of cell therapy is predicated on the effects of a single cell dose, the idea that the full therapeutic effects of a cell product require repeated doses is disruptive and has far-reaching implications. For example, inadequate dosing (single-dose protocols) may be responsible, at least in part, for the borderline or disappointing results obtained to date in clinical trials; furthermore, future studies (both preclinical and clinical) may need to incorporate repeated cell administrations. Another disruptive idea, supported by emerging preclinical and clinical evidence, is that intravenously injected cells can produce beneficial effects on the heart, presumably via release of paracrine factors in extracardiac organs or endocrine factors into the systemic circulation. Intravenous administration would obviate the need for direct delivery of cells to the heart, making cell therapy simpler, cheaper, safer, more scalable, and more broadly available, even on an outpatient basis. Although the mechanism of action of cell therapy remains elusive, there is compelling in vitro evidence that transplanted cells modulate the function of various immune cell types via release of paracrine factors, such as extracellular vesicles, although in vivo evidence is still limited. Investigation of the new paradigms reviewed herein should be a top priority because it may profoundly transform cell therapy and finally make it a reality.